Inhibition of release of inflammatory mediators in primary and cultured cells by a Chinese herbal medicine formula for allergic rhinitis - McPhee Sarah; Thien Frank CK; Story David F; Xue Charlie CL; Lenon George B; Li Chun G (BMC, 2007)
Abstract Background We demonstrated that a Chinese herbal formula, which we refer to as RCM-101, developed from a traditional Chinese medicine formula, reduced nasal and non-nasal symptoms of seasonal allergic rhinitis (SAR). The present study in primary and cultured cells was undertaken to investigate the effects of RCM-101 on the production/release of inflammatory mediators known to be involved in SAR. Methods Compound 48/80-induced histamine release was studied in rat peritoneal mast cells. Production of leukotriene B4 induced by the calcium ionophore A23187 was studied in porcine neutrophils using an HPLC assay and lipopolysaccharide-stimulated prostaglandin E2 production was studied in murine macrophage (Raw 264.7) cells by immune-enzyme assay. Expression of cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) was determined in Raw 264.7 cells, using western blotting techniques. Results RCM-101 (1-100 μg/mL) produced concentration-dependent inhibition of compound 48/80-induced histamine release from rat peritoneal mast cells and of lipopolysaccharide-stimulated prostaglandin E2 release from Raw 264.7 cells. Over the range 1 - 10 μg/mL, it inhibited A23187-induced leukotriene B4 production in porcine neutrophils. In addition, RCM-101 (100 μg/mL) inhibited the expression of COX-2 protein but did not affect that of COX-1. Conclusion The findings indicate that RCM-101 inhibits the release and/or synthesis of histamine, leukotriene B4 and prostaglandin E2 in cultured cells. These interactions of RCM-101 with multiple inflammatory mediators are likely to be related to its ability to reduce symptoms of allergic rhinitis.